Enhanced Antitumor Response to Immune Checkpoint Blockade Exerted by Cisplatin-Induced Mutagenesis in a Murine Melanoma Model - Gorgun, Falih M.; Widen, Steven G.; Tyler, Douglas S.; Englander, Ella W. (Frontiers in Oncology, 2021)
Sequencing data from different types of cancers including melanomas demonstrate that tumors with high mutational loads are more likely to respond to immune checkpoint blockade (ICB) therapies. We have previously shown that low-dose intratumoral injection of the chemotherapeutic DNA damaging drug cisplatin activates intrinsic mutagenic DNA damage tolerance pathway, and when combined with ICB regimen leads to tumor regression in the mouse YUMM1.7 melanoma model. We now report that tumors generated with an in vitro cisplatin-mutagenized YUMM1.7 clone (YUMM1.7-CM) regress in response to ICB, while an identical ICB regimen alone fails to suppress growth of tumors generated with the parental YUMM1.7 cells. Regressing YUMM1.7-CM tumors show greater infiltration of CD8 T lymphocytes, higher granzyme B expression and higher tumoral cell death. Similarly, ex-vivo, immune cells isolated from YUMM1.7-CM tumors-draining lymph nodes (TDLNs) co-incubated with cultured YUMM1.7-CM cells, eliminate the tumor cells more efficiently than immune cells isolated from TDLNs of YUMM1.7 tumor-bearing mice. Collectively, our findings show that in vitro induced cisplatin mutations potentiate the antitumor immune response and ICB efficacy, akin to tumor regression achieved in the parental YUMM1.7 model by ICB administered in conjunction with intratumoral cisplatin injection. Hence, our data uphold the role of tumoral mutation burden in improving immune surveillance and response to ICB, suggesting a path for expanding the range of patients benefiting from ICB therapy.